Signalling change: Micro insights on the pathways to agricultural transformation - Parvathi, Priyanka; Amare, Mulubrhan; Nguyen, Trung Thanh; Barrett, Christopher B. (International Food Policy Research Institute, 2019)
Most studies of agricultural transformation document the impact of agricultural productivity on macroeconomic indicators of development. Much less is known about the micro-scale changes within the farming sector that signal a transformation precipitated by exogenous agricultural productivity growth. This study identifies early trends in the agricultural sector that indicate an onset of structural change. We also comparatively analyse the patterns of micro-level changes between Sub-Saharan African (SSA) farmers and rural smallholders in Southeast Asia (SEA). We use panel data from the Living Standard Measurement Study – Integrated Survey on Agriculture (LSMS-ISA) on Uganda and Malawi and from the Thailand Vietnam Socio-economic panel (TVSEP). We apply a fixed effects instrumental variable regression to identify the exogenous component of the agricultural productivity shock. Results indicate that exogenous increases in lagged agricultural income improve average village off-farm income and trigger a change in cultivation patterns within the agrarian sector in both SEA and SSA. However, we find that the patterns of transformation are not uniform across countries.